Proceedings of the 2008 SIAM International Conference on Data Mining 2008
DOI: 10.1137/1.9781611972788.9
|View full text |Cite
|
Sign up to set email alerts
|

Mining Association Rules of Simple Conjunctive Queries

Abstract: We present an algorithm for mining association rules in arbitrary relational databases. We define association rules over a simple, but appealing subclass of conjunctive queries, and show that many interesting patterns can be found. We propose an efficient algorithm and a database-oriented implementation in SQL, together with several promising and convincing experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 15 publications
0
47
0
Order By: Relevance
“…Recently, we have considered association rule mining on arbitrary relational databases by combining pairs of queries which could reveal interesting properties in the database [8,13]. Intuitively, we pose two queries on the database such that one query is more specific than the other (w.r.t.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have considered association rule mining on arbitrary relational databases by combining pairs of queries which could reveal interesting properties in the database [8,13]. Intuitively, we pose two queries on the database such that one query is more specific than the other (w.r.t.…”
Section: Introductionmentioning
confidence: 99%
“…The Conqueror algorithm recently developed by Goethals et al [8] has shown to discover interesting association rules over a simple, but appealing subclass of conjunctive queries, called simple conjunctive queries. Furthermore, the algorithm had an efficient database-oriented implementation in SQL.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations